1978
DOI: 10.1002/eji.1830080514
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of B lymphocyte function. VI. Ontogeny of thymus cell capacity to facilitate the functional maturation of B lymphocytes

Abstract: The differentiation of the B cell population from fetal mice to produce a normal, adult-like, heterogeneous reponse, with respect to antibody affinity, has been shown to require (or to be facilitated by) thymus cells. The maturation of the thymus cell population to be capable of facilitating this differentiation of the B cell population was studied. It was found that the thymus cell population acquires the capacity fo facilitate (or induce) this maturation of the B cell population between seven and ten days af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Studies using various inbred mouse strains have shown that the maturation of antibody avidity is regulated genetically and may vary between different individuals [17–19]. The cellular immune system, together with cytokines and the Th1/Th2 balance, may play an important role in this regulation and, for example, interferon‐gamma has been shown to augment avidity maturation [20–22]. High avidity antibodies are more effective in virus neutralization [23,24], which is important for immunity against enterovirus infections.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using various inbred mouse strains have shown that the maturation of antibody avidity is regulated genetically and may vary between different individuals [17–19]. The cellular immune system, together with cytokines and the Th1/Th2 balance, may play an important role in this regulation and, for example, interferon‐gamma has been shown to augment avidity maturation [20–22]. High avidity antibodies are more effective in virus neutralization [23,24], which is important for immunity against enterovirus infections.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of somatic mutation may relate to T cell dependence of the ontogeny of normal B cell functional maturation. Mouse B lymphocytes acquire the capacity to give a normal adult-like heterologous response between 7 and 10 d of age (32,33), and this functional maturation is independent of antigenic drive since it is observed in germ-free mice (34). In a model using irradiated mice, reconstituted with adult thymocytes and B cells from fetal liver and adult spleen, the maturation of B cells to produce antibodies with heterogenous affinities is shown to depend on cells derived from thymus.…”
Section: Discussionmentioning
confidence: 99%
“…It was further shown that immature B cells acquire the capacity to give a high-affinity PFC response only if adult thymus cells are given to the irradiated mice together with the immature B cells [20]. It was established that the thymus cell population acquires the capacity to facilitate maturation of the BCP between 7 and 10 days after birth [34]. Thus, maturation of the BCP appears to be regulated by maturation of the thymus.…”
Section: Discussionmentioning
confidence: 99%